2010
DOI: 10.1186/1752-1947-4-400
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous infiltration of a parathyroid adenoma presenting as primary hyperparathyroidism in a woman: a case report

Abstract: IntroductionHypercalcemia can be associated with vitamin D (1,25(OH)2D3) -mediated granulomatous disorders in addition to primary hyperparathyroidism (PHPT). Although most patients with granulomatous disease-related hypercalcemia are asymptomatic, symptoms and signs of chronic hypercalcemia can occur. There are many reports about co-presentation of a parathyroid adenoma and a granulomatous disorder in the literature. However, granulomatous inflammation within a parathyroid adenoma is very rare.Case presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A hand search of article bibliographies was also performed with the ISI Thompson Web of Knowledge Citation report, enabling further articles to be retrieved. From the initial electronic search of 185 articles for possible inclusion, 27 articles were retained following title and abstract reviews; these articles reported on a total of 96 patients with inflammatory diseases of the parathyroid gland, including parathyroiditis ( n = 15), lymphocytic infiltrate ( n = 69), sarcoidosis of the parathyroid gland ( n = 6), tuberculosis ( n = 14), and granulomatous disease ( n = 2) 10–36 . The inclusion criterion was unambiguous evidence of inflammatory processes of the parathyroid gland in the form of a histological description.…”
Section: Methodsmentioning
confidence: 99%
“…A hand search of article bibliographies was also performed with the ISI Thompson Web of Knowledge Citation report, enabling further articles to be retrieved. From the initial electronic search of 185 articles for possible inclusion, 27 articles were retained following title and abstract reviews; these articles reported on a total of 96 patients with inflammatory diseases of the parathyroid gland, including parathyroiditis ( n = 15), lymphocytic infiltrate ( n = 69), sarcoidosis of the parathyroid gland ( n = 6), tuberculosis ( n = 14), and granulomatous disease ( n = 2) 10–36 . The inclusion criterion was unambiguous evidence of inflammatory processes of the parathyroid gland in the form of a histological description.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of patients with granulomatous disease-related hypercalcemia do not present with symptoms; however, in some cases, chronic hypercalcemia may occur (6). To date, at least to the best of our knowledge, only eight cases of granulomatous inflammation of the parathyroid gland caused by TB have been reported in the literature (4,(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory lesions of the parathyroid gland, particularly granulomas involving the parathyroid gland are very rare and seldom described. Hypercalcaemia occurring due to granulomatous disease remains asymptomatic; however, features of chronic hypercalcaemia may occur under long-standing conditions 1. Although rare, thymic tissue is commonly associated with the thyroid and parathyroid gland due to its faulty descent.…”
Section: Introductionmentioning
confidence: 99%